Chicory Taproot Production: Effects of Biostimulants under Partial or Full Controlled Environmental Conditions - Gabriele Paglialunga; Simona Proietti; Mariateresa Cardarelli; Stefano Moscatello; Giuseppe Colla; Alberto Battistelli (Agronomy, 2022)
Two trials were conducted on chicory (Cichorium intybus L.) grown under greenhouse and growth chamber conditions with the aim to evaluate the potential of three biostimulants (seaweed extract (SWE), animal-derived protein hydrolysate (APH), and vegetal-derived protein hydrolysate (VPH) on improving quali-quantitative traits of taproot, in short and out-of-season production cycles. In the greenhouse trial, VPH biostimulant promoted the inulin yield on a per-hectare basis with respect to the untreated control and APH. Taproot fresh weights, dry weights, and diameter in VPH-treated plants increased in comparison with APH-treated ones. SWE-treated plants showed intermediate values of the root production parameters and the inulin yield, with no statistical difference with VPH, APH, and control. In the growth room trial, SWE, VPH, and control showed no significant differences in growth, root yield, and quality. The results demonstrated that VPH can be useful for improving root production and inulin yield of chicory under partial controlled conditions such as in a greenhouse, whereas no benefits of biostimulant applications on crop yield and quality traits were recorded in growth chambers under full control of micro-climate conditions.